2021
DOI: 10.1177/0013916521995480
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Fit and User Behavior in Activity-Based Work Environments

Abstract: While activity-based working is gaining popularity worldwide, research shows that workers frequently experience a misfit between the task at hand and their work setting. In the current study, experience sampling data were used to examine how perceived fit in activity-based work environments is related to user behavior (i.e., the use of work settings and setting-switching). We found that workers’ perceived fit was higher when they used closed rather than open work settings for individual high-concentration work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…It appears as though flexible and interactive work tasks are appropriate for an AFO environment whereas individual tasks demanding a high degree of concentration are less suitable. Furthermore, the facilitation and access to quiet areas and closed work settings for concentration intensive work seems to be of great importance as has been highlighted in previous studies [16,32]. Another factor that has been associated with possible impact on productivity in AFOs, is the time that employees spend searching for a workstation.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…It appears as though flexible and interactive work tasks are appropriate for an AFO environment whereas individual tasks demanding a high degree of concentration are less suitable. Furthermore, the facilitation and access to quiet areas and closed work settings for concentration intensive work seems to be of great importance as has been highlighted in previous studies [16,32]. Another factor that has been associated with possible impact on productivity in AFOs, is the time that employees spend searching for a workstation.…”
Section: Discussionmentioning
confidence: 91%
“…However, employees' satisfaction with communication, as well as privacy, also affect productivity in AFOs [15]. In a recent study, Hoendervanger et al [16], showed that it seems to be particularly important to optimize the workers perceived fit and user behavior, to facilitate and stimulate individual high-concentration work. Interestingly, no longitudinal studies have investigated if and how productivity in AFOs is influenced depending on the actual work tasks.…”
Section: Introductionmentioning
confidence: 99%
“…ABW environments have seen a rise over the last years. This type of workspace design is thoroughly reviewed in recent literature, primarily in respect to their impact on productivity, employees' satisfaction and Person-Environment fit [ [38] , [39] , [40] , 97 ]. The results of this exploratory survey suggest that the use of ABW environments will increase in the post-pandemic future.…”
Section: Resultsmentioning
confidence: 99%
“…The working places from which employees have to choose in mobile work and activity‐based offices tend to differ with regard to how well they fit certain tasks and employees' needs. For example, a quiet desk at home might be well suited for tasks requiring intense concentration, whereas a workplace in an open office might better fit tasks requiring frequent consultations with colleagues (Hoendervanger et al, 2021 ). As employees are responsible for planning and deciding where they work according to their tasks and needs, they face cognitive demands arising from planning their working place (Prem et al, 2021 ).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%